The Associations Between Patients' Characteristics and the Quality of Life Among Acute Coronary Syndrome Patients in Jordan: A Cross-Sectional Study - Mohannad A. Aljabery MSN, RN; Ahmad Rajeh Saifan RN, PhD; Intima Alrimawi PhD, RN; Ahmad Mahmoud Alzoubi MSN, RN; Maha Atout PhD, RN (SAGE Publishing, 2022)
Introduction Acute coronary syndrome (ACS) is one of the most significant leading causes of death and disability in the world. The quality of life (QoL) score is used to evaluate the impact of ACS treatments on the patients' physical, emotional, and social functioning. It is considered a significant indicator of the progress of the patients' health status and is useful in predicting patients' needs for continuing, modifying, or changing their treatment plans. Objective To identify the associations between patients' characteristics and the QoL among ACS patients in Jordan. Methods A descriptive cross-sectional study was conducted using a convenience sample of 372 participants with ACS from six referral hospitals in Jordan. Results Jordanian patients with higher educational level and exercise had significant and positive association with QoL (β = 0.257, p  < .001), (β = 0.191, p  < .001), respectively. Also, patients who reported having dyslipidaemia and having unstable angina (UA) had lower score of QoL (β = −0.165, p  < .001), (β = −0.149, p  < .001), respectively. Finally, gender and working status did not significantly appear to have an association with the total QoL. Conclusions This study sheds light on the importance of increasing the level of patients' awareness about their illness by educating them about it and encouraging them to engage in physical activity programs.